Bleb-related Infection following Trabeculectomy - Thapa, Madhu; Gautam, Pragati; Pachai, Sareena (Nepalese Journal of Ophthalmology, 2025)
Introduction: Bleb-related endophthalmitis after trabeculectomy is a rare but sight threatening complication. Thin walled blebs, occurring after adjunctive use of antimetabolite like mitomycin C and 5-flurouracil, is an important risk factor for bleb-related infections.Case: Forty-five years old one-eyed male had undergone trabeculectomy in past, had presented with diminution of vision, pain, photophobia in his seeing eye.Observation: On examination, best corrected visual acuity was 5/60, thin walled avascular bleb with congested conjunctiva, minimal hypopyon, pupil had fibrinous exudate and vitreous reaction. He was diagnosed as bleb-related endophthalmitis. He improved after intra-vitreal and topical antibioticsConclusion: Bleb-related infections can be controlled if diagnosed and treated on time.